How Ethical Is Our Research Ethics? A Point To Ponder - Farah Ahmad; Ibtisam Qazi (ziauddin University, 2024)
The health of the common man, an oft-neglected issue in many developing countries, is marked by rampant corruption and gross neglect on the part of the very institutions delegated with this responsibility. It is rather unfortunate that Bioethics, despite being recognized as an important discipline and being around for more than 40 years, when there is a need to be reinforced in developing countries there is a blatant disregard for the ethical principles.